Estimation of the Deflection Angle of Plate Driven by the Products of Grazing Detonation - Trzciński, W.A. (Engineering Transactions, 1999)
The deflection angle of a metal plate launched by the products of detonation grazing along the surface of the plate has been estimated theoretically. The influence of parameters characterising the plate and an explosive charge on quantitative characteristics of the launching process has been analysed. Results of the numerical calculations presented in the form of diagrams enable simple estimation of a dynamic deflection angle of the plate for given parameters of the explosive system. Estimated values of the angle can be applied in construction of the explosive schemes destined for cladding and strengthening purposes.